Patent Foramen Ovale (PFO), Personality Traits, and Iterative Decompression Sickness. Retrospective Analysis of 209 Cases - Lafère, Pierre; Balestra, Costantino; Caers, Dirk; Germonpré, Peter (Frontiers in Psychology, 2017)
Introduction: There is a need to evaluate the influence of risk factors such as patency of foramen ovale (PFO) or “daredevil” psychological profile on contra-indication policy after a decompression sickness (DCS). Methods: By crossing information obtained from Belgian Hyperbaric Centers, DAN Emergency Hotline, the press and Internet diving forums, it was possible to be accountable for the majority if not all DCS, which have occurred in Belgium from January 1993 to June 2013. From the available 594 records we excluded all cases with tentative diagnosis, medullary DCS or unreliability of reported dive profile, leaving 209 divers records with cerebral DCS for analysis. Demographics, dive parameters and PFO grading were recorded. 23 injured divers were tested using the Zuckerman’s Sensation Seeking Scale V and compared to a matched group not involved in risky activities. Results: 41.2% of all injured came for iterative DCS. The average depth significantly increases with previous occurrences of DCS (1st DCS: 31.8±7.9 mfw; 2nd DCS: 35.5±9.8 mfw; 3rd DCS: 43.4±6.1 mfw). There is also an increase of PFO prevalence among multiple injured divers (1st DCS: 66.4% 2nd & 3rd DCS: 100%) with a significant increase in PFO grade. Multiple-times injured significantly scored higher than control group on thrill and adventure seeking, experience seeking, boredom susceptibility and total score. Conclusion: There is an inability of injured diver to adopt conservative dive profile after a DCS. Further work is needed to ascertain whether selected personality characteristics or PFO should be taken into account in the clearance decision to resume diving.